Ethnomathematics Exploration on Purun Crafts of Pulau Geronggang for Middle School Mathematics Learning - Saputro, Adi; Somakim, Somakim; Darmawijoyo, Darmawijoyo (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2023)
Mathematical concepts sometimes arise naturally through the culture of a particular community. Mathematics with cultural nuances (ethnomathematics) will contribute greatly to learning mathematics. Ethnomathematics can be used to make it easier for students to learn through a cultural approach. This research aims to: 1) Find out what mathematical concepts are found in the Purun craft of Geronggang Island. 2) Find out what philosophical values are present in the Purun craft of Geronggang Island. 3) Find out how junior high school mathematics learning can be implemented within the context of ethnomathematics in the Purun craft of Geronggang Island. In research data collection, researchers are directly involved in the data collection process through interviews, observation, and documentation. Data was analyzed by carrying out data reduction, data presentation, and data exploration. Variants of shapes and types of Geronggang Island purun crafts contain several aspects of mathematics on geometric material.